Taxonomic reexamination of Portulaca okinawensis (Portulacaceae) inthe Ryukyu Archipelago of Japan based on molecular and morphological data - Kokubugata, Goro; Nakamura, Koh; Hirayama, Yumiko; Yokota, Masatsugu (Phytotaxa, 2013)
We used molecular phylogenetic and morphological data to reexamine the taxonomic status of Portulaca okinawensis (≡ P. pilosa subsp. okinawensis) endemic to the central Ryukyu islands, southwestern Japan. Our molecular analyses showed that P. okinawensis is monophyletic, sister to the clade of P. psammotropha and P. tuberosa and it is not closely related to P. pilosa subsp. pilosa. Two subclades, one comprising plants from the Okinawa Islands and the other from the Amami Islands, were recognized. The plants from the Okinawa Islands had more than 20 stamens, orange-yellow nallowly obovate to oblanceolate petals, and reddish-green stems (as the holotype), while the plants from the Amami Islands had less than 20 stamens, lemon-colored obovate petals, and bright-green stems. The molecular and morphological data support a taxonomic treatment of Walker & Tawada (1951) regarding P. okinawensis as a separate species, also suggesting that the plants from the Amami and Okinawa islands should be treated as different taxa. A new variety Portulaca okinawensis var. amamiensis was here described.